Improving Natural Science Cognitive Learning Outcomes Through the Make-A-Match Learning Model - Firman Ferdiansyah; Wiwik Rumiati (Universal Education Jurnal Teaching and Learning, 2024)
This research is based on the finding that the cognitive learning outcomes of fourth grade students in natural sciences subjects are still very low. This study aims to improve students' cognitive learning outcomes in science subjects by applying the Make-a-Match learning model. This study used classroom action research. The research was conducted on 24 fourth grade students in one of the elementary schools in Tanjung Jabung Barat Regency. The research was conducted in two cycles: planning, implementation, observation, and reflection. The instruments used in this study were cognitive learning outcomes test questions, observation sheets, and interview guidelines. The results showed that students' learning outcomes improved, based on the average score of cognitive learning outcomes they obtained, namely 50.5 in pre-cycle, 74.21 in cycle I, and 81.04 in cycle II. In addition, students are more active in participating in learning that applies the make-a-match learning model.